The Analisis Job Satisfaction, Job Insecurity dan Turn Over Intention Studi kasus pada PT Indomarco Prismatama Magelang - Irfatah, Mohamad; Kurniawati, Agustaria; Wening, Nur (P4M STIE Putra Bangsa, 2019)
Good human resource management needs to be done in order to retain employees who show performance so they do not have the desire to leave and or resign (turnover intention) to other companies and or competitors. The objectives of this study are: (1) To find out and analyze Job Satisfaction of PT Indomarco Prismatama employess in Magelang City; (2) Know and analyze Job insecurity of employees of PT Indomarco Prismatama in Magelang City; (3) Know and analyze Turnover Intention of employees of PT Indomarco Prismatama in Magelang City. This research is a quantitative descriptive research using the employees of PT Indomarco Prismata- ma in Magelang City, the research is based upon 50 respondents who are permenant employress of PT. Indomarco Prrsmatama in Magelang City. The analytical method used in the research is descriptive statistical analysis. The results of the analysis show that on average, with regards to Job Satisfaction; employees felt very good at PT Indomarco Prismatama in Magelang City. However, Job Insecurity at PT Indomarco Prismatama in Magelang City is low, and turnover intention of PT Indomarco Prismatama employees in Magelang City is low. Keywords: Job Satisfaction, Job Insecurity, Turnover Intention